Valuating intangible benefits from afforested areas: A case study in India - Avinash Jain; Girish Chandra; Raman Nautiyal (Economía Agraria y Recursos Naturales)
Environmental compensation measures usually accompany energy projects. Willingness-To-Pay (WTP) for five intangible benefits derived from afforested areas of a compensatory afforestation programme of National Thermal Power Corporation Dadri are estimated. Conventional Contingent Valuation shows the average WTP â‚¬ 2.1 per respondent per month with more than 43 % of total WTP for ‘soil conservation and remediation’ and ‘improvement in underground water level’. Logit model method depicts the same order of magnitude but differs significantly at 5 % level for all the benefits. More informed decisions upon energy projects and afforestation programs shall help in conserving forests and their ecosystem services.